Mapping end-of-life and anticipatory medications in palliative care patients using a longitudinal general practice database. Issue 1 (February 2022) - Khalil, H.; Garett, M.; Byrne, A.; Poon, P.; Gardner, K.; Azar, D.; Craig, L.; Karimi, L.
Abstract: Objective: End-of-life and anticipatory medications (AMs) have been widely used in various health care settings for people approaching end-of-life. Lack of access to medications at times of need may result in unnecessary hospital admissions and increased patient and family distress in managing palliative care at home. The study aimed to map the use of end-of-life and AM in a cohort of palliative care patients through the use of the Population Level Analysis and Reporting Data Space and to discuss the results through stakeholder consultation of the relevant organizations. Methods: A retrospective observational cohort study of 799 palliative care patients in 25 Australian general practice health records with a palliative care referral was undertaken over a period of 10 years. This was followed by stakeholders' consultation with palliative care nurse practitioners and general practitioners who have palliative care patients. Results: End-of-life and AM prescribing have been increasing over the recent years. Only a small percentage (13.5%) of palliative care patients received medications through general practice. Stakeholders' consultation on AM prescribing showed that there is confusion about identifying patients needing medications for end-of-life and mixed knowledge about palliative care referral pathways. Significance of results: Improved knowledge and information around referral pathways enabling access to palliative care services for general practice patients and their caregivers are needed. Similarly, the increased utility of screening tools to identify patients with palliative care needs may be useful for health care practitioners to ensure timely care is provided.